Genetics of Attention Deficit Hyperactivity Disorder: A current review and future prospects - Levy, F.; Hay, David; Bennett, Kellie (Routledge, 2006)
While there have been significant advances in both the behaviour genetics and molecular genetics of Attention Deficit Hyperactivity Disorder (ADHD), researchers are now beginning to develop hypotheses about relationships between phenotypes and genetic mechanisms. Twin studies are able to model genetic, shared environmental and non-shared environmental influences on aetiology. The present review describes recent behaviour genetic and latent class findings in relation to ADHD and its subtypes, including rater effects, comorbidity, and developmental effects, which have an impact on findings of high heritability. Molecular genetic studies have predominantly focused on dopamine genes, including dopamine receptor and transporter genes, because of animal and human studies indicating the importance of dopaminergic attention systems. The recent clinical use of noradrenergic reuptake inhibitors has also increased interest in noradrenergic genes. Adult ADHD and age-related genetic effects, in addition to “reading” genes, are reviewed in relation to comorbidity and developmental effects.